TEDUGLUTIDE - A GLP-2 ANALOG IN THE TREATMENT OF SHORT BOWEL SYNDROME: A LITERATURE REVIEW - Kamil Harenza,; Mateusz Taranowicz,; Olga Kowalczyk,; Dominika Zdobylak,; Monika Kowalska,; Anita Zięba,; Michał Domin,; Justyna Całka,; Katarzyna Ścibisz,; Karolina Ollik, (International Journal of Innovative Technologies in Social Science, 2026)
Short bowel syndrome–associated intestinal failure (SBS-IF) is a rare but severe clinical condition characterized by insufficient intestinal absorptive capacity and frequent dependence on long-term parenteral support. Prolonged reliance on parenteral nutrition is associated with substantial morbidity, underscoring the need for targeted therapeutic strategies that enhance intestinal adaptation and reduce intravenous support requirements. Advances in the understanding of gut-derived trophic hormones have identified glucagon-like peptide-2 (GLP-2) as a key regulator of intestinal growth and function, leading to the development of GLP-2–based pharmacological therapies.The aim of this narrative literature review is to critically synthesise current evidence regarding the physiological role of GLP-2, the pharmacological properties of teduglutide, and its clinical efficacy and safety in the management of SBS-IF. A comprehensive literature search was conducted using PubMed and Google Scholar, including randomised controlled trials, observational studies, systematic reviews, and meta-analyses relevant to GLP-2 biology and teduglutide therapy.The available evidence demonstrates that teduglutide enhances intestinal absorptive capacity, promotes mucosal adaptation, and enables clinically meaningful and sustained reductions in parenteral support requirements in both adult and paediatric patients. In selected individuals, treatment may facilitate partial or complete achievement of enteral autonomy. However, given its intestinotrophic mechanism of action, appropriate patient selection, structured monitoring, and long-term safety surveillance remain essential. Overall, teduglutide represents a significant advance in the targeted treatment of SBS-associated intestinal failure.